Pengaruh Ulasan Positif dan Ulasan Negatif Produk di E-Commerce Shopee Terhadap Keputusan Pembelian Konsumen (Studi Kasus di Fakultas Ekonomi dan Bisnis Universitas Singaperbangsa Karawang) - Amaldin, Amalya Dwi Putri; Ratnasari, Ina (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This case study focuses on students at the Faculty of Economics and Business, Singaperbangsa University, Karawang. The aim of this research is to evaluate how positive and negative product reviews on the Shopee e-commerce platform influence consumer purchasing decisions. This research was conducted using a quantitative approach and 103 students received questionnaires which were then tested using multiple linear regression. The study results show that product reviews, both positive and negative, greatly influence consumers' decisions to purchase products. Overall, positive and negative reviews accounted for 45.7% of consumers' purchasing decisions. These results indicate that product review management is critical for e-commerce companies to attract and identify customers.